Modelagem de conhecimento baseada em ontologia e dados abertos: a representação do domínio da tomada e prestação de contas anual dos gestores públicos federais - Reuber da Silva Fonseca (2023)
Faced with unprecedented technological development and the adoption of new political-administrative references by the Public Administration, this research aimed to develop a knowledge modeling based on an ontology prototype instantiated with structured open data from the knowledge domain of taking and annual accountability of federal public managers in order to support the development of civic software. In summary, the problem that arises in this study is revealed by the paradox between the vast amount of government data made available through public administrators' accountability and the low perception and appropriation of knowledge generated by citizens. It is proposed as a question to be answered: how to model the domain of knowledge of the taking and annual accountability of federal public managers in order to facilitate and accelerate the development of civic software based on structured and semantic data? This study is justified by proposing an applied research, supported by theoretical studies, of the use of a mechanism of representation of domains of knowledge, the ontology, in the solution of real world problems. In this specific case, it is justified by enabling the emergence of an open access ontology prototype that favors the development of civic software capable of investigating the efficacy, efficiency and effectiveness of public policies and services. From the methodological point of view, a qualitative exploratory research was developed with technical procedures of bibliographical and documental research. The Protégé 5.5.0 framework and the OntoForInfoScience methodology proposed by Mendonça (2015) were used to develop the prototype. As a result, the OntoAccount domain ontology was created. It is expected that the prototype represents the concepts and relationships of the domain, in addition to making it possible to answer questions about the domain of taking and annual accountability of federal public managers.